Assessment of the iodine level of table salt from Senegalese households - Diop, Amadou; Gueye, Rokhaya; Balde, Mamadou; Thiam, Khadidiatou; Tittikpina, Nassifatou Koko; Niass, Ousmane; Sarr, Serigne Omar; Ndiaye, Bara; Diop, Yerim Mbagnick (European Journal of Chemistry, 2021)
Senegal is affected by a relatively high prevalence of iodine deficiency disorders, which compromises its social and economic development. To address this situation, the Universal Salt Iodization strategy was adopted by the Senegalese Government. The monitoring of salt iodine status is crucial to the success of such a program. Therefore, this study aimed to evaluate the iodine concentration of table salt from Senegalese households. A total of 1575 samples collected in urban and rural areas were analyzed using the iodometric method. The powdered salt samples showed higher mean iodine content (18.99 ppm) and lower percentage of non-compliance (58.4%) than the other salt types (p = 0.02). Most of the samples collected from urban area were found with iodine content between 15 and 39.9 ppm, whereas, in rural areas, the situation was significantly different (p = 0.01). Iodine levels of most samples were lower than 5 ppm in the rural producing area or varied between 5 to 14.9 ppm in the rural non-producing area. A percentage of 37.3% of adequately iodized salt samples was obtained at a national scale with a significant disparity between urban and rural areas. Therefore, improvements in quality control procedures in tandem with the iodization process are necessary and an information, education and communication strategy should be adopted.